Causal structure of spatiotemporal variables and walking motion for achieving high walking speed in race-walking - Sato, T.; Ohyama-Byun, K.; Miura, K.; Kawamukai, T.; Ohkubo, R.; Ogata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2025)
The purpose of this study was to clarify the causal structure for achieving high walking speed and to obtain useful information that would contribute to race-walking coaching. Ninety-seven male race-walkers with a wide range of performance level were analyzed using motion analysis involving 3-dimensional direct linear transformation with 2 video cameras. Variables such as walking speed, step length, step frequency, joint angle, and segment angular velocity were obtained from the video images in the early phase of 3 20-km race-walking competitions. Several indices were calculated from spatiotemporal variables using the height of each athlete, and we examined the relationships among these indices. Based on these relationships, a causal structure model including the walking motion variable was developed, and the validity of this model was examined using structural equation modeling (SEM). The main results were as follows. The walking speed index and step length index showed a linear relationship with their component variables, whereas the pitch index showed a curvilinear relationship with the contact time index and flight time index. This indicated that the relationship between the pitch index and its component variables varies depending on performance level. In addition, the walking speed index was moderately to strongly correlated with both the step length index and the pitch index. Furthermore, the step length index was strongly correlated with the flight distance index and the pitch index with the contact time index. These correlations indicate that improving the flight distance index and decreasing the contact time index are important for achieving a high walking speed. The validity of the model developed in this study was high, indicating that the model represents the actual relationships among the various indices and walking motion. The model revealed that a large angular velocity of shoulder flexion on the supporting leg side and angular velocity of swing forward the recovery thigh at ground contact, and little anterior tilt of the torso at toe off, would alter the subsequent motions and increase the walking speed. The model developed in this study has revealed the causal structure for achieving high walking speed in race-walking as a series of motions, which may provide useful information for coaching while considering walking motion as a whole.